Risk factors for ineffective renal perfusion among elderly hospitalized in an ICU: DOI: 10.15343/0104-7809.20194303544565 - Amaral Montanari, Lilian (2019)
Acute kidney injury (AKI) is defined as a syndrome characterized by sudden and potentially reversible loss of kidney function, leading to accumulation of nitrogenous substances (urea and creatinine). The aim of this study was to identify factors related to the risk of ineffective renal perfusion, showing associations with clinical and therapeutic characteristics. This was a retrospective, cross-sectional study with a descriptive and correlational analysis conducted in a general adult intensive care unit (ICU) of a large private hospital. The convenience sample consisted of 288 patients. All medical records of elderly patients who were admitted to the ICU from November 2016 to January 2017, regardless of their clinical diagnosis, were included. To statistically analyze the relationship between the covariates and the change in serum ICU admission and discharge values from the ICU, the ANOVA and Chi-squared tests were used. Among elderly inpatients, individuals aged between 60 and 89 years were concentrated and were mostly female. Regarding the epidemiological profile, there were more diabetes mellitus and systemic arterial hypertension comorbidities. It is noted that the elderly were exposed to many risk factors for AKI during hospitalization. The covariates that showed statistically significant results when compared with the change in urea values at ICU admission and discharge were gender, age, pre-existing nephropathies, SAH, DM and neoplasms. When the comparison was made between the covariates and the change in creatinine values, only the health problems represented by hypertension, DM, CHF and neoplasms had significant results. In this context, it is essential that nurses properly identify and plan care in the presence of risk factors for the development of AKI.